2020
DOI: 10.3390/foods9111614
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization, Antioxidant and Antimicrobial Properties of Goji Berries Cultivated in Serbia

Abstract: Since the fruits of Lycium L. species (Fructus Lycii, goji berries) are promoted as a “superfood” with plenty of health benefits, there is extensive research interest in their nutritional and phytochemical composition. In the present study, the nutritional value, minerals, fatty acid composition, and bioactive compounds of L. barbarum L., red, yellow, and black goji berry (L. ruthenicum Murray.) cultivated in Serbia were investigated. Antioxidant and antimicrobial properties of their methanol extracts were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 56 publications
1
41
0
Order By: Relevance
“…In our study, the protein content of goji berry was determined as 13.18%. In similar studies, the content of protein in fresh goji berry Ilić et al (2020) 2020) 3.5-20.3% found it to be. Our conclusion is consistent with the data from previous studies, that goji berries have significant potential to provide the required daily protein for adults (0.8 g/kg body weight).…”
Section: Protein Contentmentioning
confidence: 73%
See 2 more Smart Citations
“…In our study, the protein content of goji berry was determined as 13.18%. In similar studies, the content of protein in fresh goji berry Ilić et al (2020) 2020) 3.5-20.3% found it to be. Our conclusion is consistent with the data from previous studies, that goji berries have significant potential to provide the required daily protein for adults (0.8 g/kg body weight).…”
Section: Protein Contentmentioning
confidence: 73%
“…The pH and titratable acidity of goji berries were determined as 5.18% and 2.16%, respectively. Zhang et al (2016) determined the titratable acidity of goji berry fruit 0.8-1.4%, Ilić et al (2020) 0.70-0.89%, Catav and Pırlak (2020) determined it as 0.05-0.19. It is seen in our study that the titration acidity value is within the range of the reported values.…”
Section: Titration Acidity and Ph Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the single classes of unsaturated fatty acids, di-unsaturated fatty acids (DUFA) were measured as the most abundant, showing the same content in the BL cultivar and a slight increase in SL. Mono-unsaturated fatty acids (MUFA) generally increased during the time for both cultivars, with the lowest content measured in SL1 that, on the contrary, was characterized by the highest amount of tri-unsaturated fatty acids (TUFA), generally present in low concentrations [ 30 , 31 ]. Regarding polar lipids, the BL cultivar showed an increase of digalactosyldiacylglycerol (DGDG) and a decrease in phosphatidylcholine (PC) during the time.…”
Section: Resultsmentioning
confidence: 99%
“…The Lycium fruits contain phenolics, flavonoids, organic acids, and fatty acids (Wang et al, 2010;Mikulic-Petkovsek et al, 2012) and are also high in vitamins such as thiamine, riboflavin, and vitamin C (Donno et al, 2014;Niro et al, 2017), carotenoids , polysaccharides (Luo et al, 2004;Wang et al, 2010), betaine (Xie et al, 2001;Lee et al, 2014;Qian et al, 2017), and taurine (Potterat, 2010), have high mineral concentrations (Grembecka & Szefer, 2013). With such a rich biochemical composition, goji fruits are very widely used in pharmacology due to their high anti-cancer (Tang et al, 2012;Cumaoglu et al, 2018), anti-hyperglycemic (Potterat, 2010;Wojdyło et al, 2018), anti-inflammatory (Liu et al, 2015;Wang et al, 2017), anti-aging properties Wojdyło et al, 2018), and antioxidant properties (Illić et al, 2020). Not only do the fruits contain biologically active substances, but also other parts of plants, especially leaves (Chen et al, 2020;Szot et al, 2020).…”
Section: Introductionmentioning
confidence: 99%